Slovenia and its relations with Russia in the Euro-Atlantic context - Benedejčič, Andrej (Teorija in praksa, 2016)
Among the new EU and NATO members Slovenia is known for its "friendly pragmatism" in its relations with Russia. This can be explained as a manifestation of a recurring pattern in identity politics, typical of smaller Slavic nations of Central and South-Eastern Europe. In this sense, the case of Slovenia demonstrates the utility of social constructivism in international relations theory and corroborates the importance of social identities in the formation of intra-state policies and security communities. It also has clear implications for the process of Euro- Atlantic integration in the future, especially as it relates to Slavic candidate countries - unwarranted delays on this path can have unintended consequences.
Keywords: Bilateral relations; Bilateralni odnosi; European Union; Evropska unija; International relations; Mednarodni odnosi; NATO; Rusija; Russia; Slovenia; Slovenija